2022
DOI: 10.3390/children9081188
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Manifestations of Dental Ankylosis in Primary Molars Using Panoramic X-rays: A Cross-Sectional Study

Abstract: Dental ankylosis is a serious condition defined as the process that causes the fusion between the dentin or the cementum of the root and the alveolar bone, with the obliteration of the periodontal ligament becoming progressively replaced by bone tissue. The aim of the study was to determine the prevalence, location, severity, and association of dental ankylosis in primary molars with other dental anomalies such as the agenesis of permanent buds. For this study 150 panoramic x-rays were selected from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Our findings showed that the COS is deepened in the presence of a deciduous tooth (ppM2). Thus, clinicians should keep in mind that neighboring teeth may tip towards the primary tooth in consequence of its lower marginal ridges, which deepens the COS. As the first primary molar is determined as the most affected tooth affected by ankylosis [24], the presence of a deep COS might be the first sign which must be followed in a timely manner to prevent further complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that the COS is deepened in the presence of a deciduous tooth (ppM2). Thus, clinicians should keep in mind that neighboring teeth may tip towards the primary tooth in consequence of its lower marginal ridges, which deepens the COS. As the first primary molar is determined as the most affected tooth affected by ankylosis [24], the presence of a deep COS might be the first sign which must be followed in a timely manner to prevent further complications.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment should be based on the evaluation of growth potential jeopardized by the condition. Early extraction and subsequent space management, especially in the younger patient, is recommended [14] .…”
Section: Discussionmentioning
confidence: 99%
“…A tooth displaced into the maxillary sinus may cause inflammation of the maxillary sinus or imply the development of cystic tumors. Infraoclussion of teeth may cause impairment of the stomatognathic system and the occurrence of malocclusions at the dental and dentoalveolar level—open bite, crossbite, overhanging bite, and others [ 4 , 5 , 20 , 21 , 22 , 23 ].…”
Section: Diagnostics and Treatmentmentioning
confidence: 99%